Патогенез пресорних виразок у хворих на цукровий діабет і можливості їх профілактики - Ларін, О. С.; Таран, Є. В.; Юзвенко, Т. Ю.; Гирявенко, О. Я.; Гаврецький, А. І. (Clinical Endocrinology and Endocrine Surgery, 2012)
Lecture describes in detail mechanisms of pressure ulcers formation in patients with diabetes mellitus with diabetic foot syndrome and ways of their prevention by using of individual orthopedic insoles of various types.